ANALISIS PENERAPAN PSAK 102 ATAS PEMBIAYAAN MURABAHAH (STUDI KASUS PADA BANK MANDIRI SYARIAH) - Putri Eka Wardani (Universitas Islam Malang, 2017)
This study aims to determine the process of murabahah financing at PT. Bank Syariah Mandiri, such as the accounting treatment and its compliance with financial accounting standards (psak) 102. Methods in this study using descriptive qualitative and the results of this study showed that in terms of recognition and measurement PT. Bank Syariah Mandiri is in conformity with PSAK 55